Effect of Load Cell Load Calibration on Electric Wheelchair - Bobby Noval Pratama (ITScience (Information Technology and Science), 2022)
A wheelchair is an assistive device for patients who are seriously injured or ill. Especially for people with disabilities or people who can't walk using their feet. For patients who experience total paralysis such as pain in the nerves to move the wheelchair, someone needs to push the wheelchair. If there is no one around the patient, the patient has difficulty moving the wheelchair using his hands and feet to change positions. In this research, an electric wheelchair has been created using a load cell control with body position as the driving output. Based on the test results, if the body leans forward then the wheelchair moves forward, if the body leans back then the wheelchair moves backwards, If the body leans to the left then the wheelchair moves to the left and if the body leans to the right then the wheelchair moves to the right. This study aims to analyze the ability of the load cell as the propulsion output of the electric wheelchair to the user's weight. In the results of the study, it can be seen that body weight can have a greater effect if the user's mass is getting heavier.